PEMBUATAN BIOGAS DENGAN VARIASI STARTER RAGI DAN KOTORAN SAPI BERBAHAN BAKU SAMPAH ORGANIK - Rachmat Subagyo; Roni Wijaya (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2017)
This study aims to determine the composition of the right starter mixture to produce optimal biogas, knowing the temperature (in digester) at the time of fermentation, knowing the effect fungal growth on the levels of biogas. Processing organic waste in small pieces given water and starter, put in bottle and covered with balloon, last process fermentation 45 days. Then samples tested using Methane Measurement System, Carbondioxide, Humidity and Temperature. Then obtained mixture 10% starter cow dung and 90% organic waste CH4 35.79 ppm and CO2 1763.34 ppm, 20% cow dung and 80% organic waste CH4 12.12 ppm and CO2 740.55 ppm, 30% cow dung and 70% organic waste, CH4 14.08 ppm and CO2 858.87 ppm, yeast 10% and organic waste 90% CH4 9.78 ppm and CO2 860.98 ppm, 20% yeast and 80% organic waste CH4 166.08 ppm and CO2 1185.35 ppm and yeast mixture 30% and 70% CH4 organic waste 16.66 ppm and CO2 927.39 ppm. The yeast mixture 20% and 80% organic waste produces most optimal CH4 with temperature in digester at fermentation 30.11 °C with value 206.76 ppm while mixture 10% cow dung and 90% organic waste produces highest CO2 at temperature 30.4 °C with value 2527.57 ppm.